2015
DOI: 10.1039/c5tc00515a
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of CsMI3:Eu2+ (M = Mg, Ca, and Sr) – a spectroscopic probe on structural distortions

Abstract: The delicate dependence of the photoluminescence properties of Eu2+ on the structure of the perovskite-analogue iodides CsMI3 (M = Mg, Ca, Sr) is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 44 publications
6
71
0
Order By: Relevance
“…The study of photoluminescence properties of Eu 2+ ‐doped CsMI 3 [M‐Mg, Ca, Sr] perovskite has revealed that the Eu 2+ ‐doped CsMgI 3 and CsSrI 3 displayed a redshift emission with respect to Eu 2+ ‐doped CsCaI 3 perovskite. Eu 2+ ‐doped CsMgI 3 crystallizes in a distorted hexagonal CsNiCl 3 structure whereas CsCaI 3 crystallizes in an orthorhombic GdFeO 3 structure and CsSrI 3 crystallizes in a filled PuBr 3 structure …”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of photoluminescence properties of Eu 2+ ‐doped CsMI 3 [M‐Mg, Ca, Sr] perovskite has revealed that the Eu 2+ ‐doped CsMgI 3 and CsSrI 3 displayed a redshift emission with respect to Eu 2+ ‐doped CsCaI 3 perovskite. Eu 2+ ‐doped CsMgI 3 crystallizes in a distorted hexagonal CsNiCl 3 structure whereas CsCaI 3 crystallizes in an orthorhombic GdFeO 3 structure and CsSrI 3 crystallizes in a filled PuBr 3 structure …”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…The divalent rare earth Eu 2+ ‐based perovskite (C 4 H 9 NH 3 ) 2 EuI 4 has been synthesized through low‐temperature solid‐state reactions . The effect of doping of rare earth metal ions such as Eu 2+ , Tm 2+ , and Yb 2+ in CsAX 3 (A‐Ca,Mg,Sr) perovskite has been investigated extensively . Another transition metal gold has been investigated for its potential in a perovskite framework.…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds may be interesting as an experimental standard for theoretical models of the electronic structure of Yb 2+ and as potential novel scintillators in accordance with the respective Eu 2+ -doped compounds. [44][45][46][47][48][49] The photoluminescence properties of Eu 2+ have already been reported in these compounds [44][45][46][47][48][49][50][51][52] which also allows a comparison between the spectroscopic properties of both divalent lanthanides. All starting materials were pre-dried in a dynamic vacuum at 200 1C overnight, respectively, to remove all water contents.…”
Section: Introductionmentioning
confidence: 99%